Agriculture after Brexit. (25th January 2022) - Helm, Dieter
Abstract: Brexit repatriates agriculture policy and subsidies after over 40 years of determination by the European Commission. The paper starts by describing the baseline at Brexit, noting the relatively small economic contribution, the problems of competitiveness given the UK's geology and geography, and the poor environmental outcomes. The scope for improvement is correspondingly large, and in particular through the impacts of the new agricultural policy based upon public money for public goods and for England, the Environmental Land Management Schemes. Larger and more long-term impacts will come through new trade agreements, through new technologies, including digitalization, robotics, and genetics, and through carbon farming and offsets. Finally, the paper sets out a framework for a future assessment of the impact of Brexit.